HUBUNGAN TINGKAT PENGETAHUAN DAN SUMBER INFORMASI DENGAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA KELUARGA DI WILAYAH KERJA PUSTU PAHANDUT SEBERANG KOTA PALANGKA RAYA TAHUN 2016 - Putria Carolina; Meilitha Carolina; Rizki Muji Lestari (EnviroScienteae, 2016)
In 2015, Kemenkes RI, PHBS case of the lowest in West Papua province amounted to 25,50% and then the West Nusa Tenggara by 29,48%. Based on the phenomenon that is found in a study by researchers at the Kelurahan Pahandut Seberang Kota Palangka Raya there are family members who smoke inside the house, around the neighborhood still looks rubbish strewn and piled up, using water from rivers, landfills less and more people use WC cemplung. The Objective Of of this Study is To analyze the Correlation of Knowledge and Resources with Application Behavior Clean and Healthy Lifestyle (PHBs) in the Family in the Work Area Pustu Pahandut Seberang Kota Palangka Raya. This research uses correlation method with cross-sectional study design and uses a sampling technique Simple Random Sampling and statistical test Spearman`S Rho with 71 respondents. Analysis of Correlation of Knowledge and Resources with Application Behavior Clean and Healthy Lifestyle (PHBs) indicates the value (P value = 0,000 < α 0,05), which means a large correlation exists between the variables of knowledge and resources with application behavior clean and healthy (PHBs). The Level of Knowledge and resources to the implementation of clean and healthy living behaviors (PHBs) showed a significant correlation between the level of knowledge and resources to the implementation of clean and healthy living behaviors (PHBs) value (P value = 0,000 < 0,05).